HISTORIOSOPHICAL DIMENSION OF DEPORTATION PROCESSES ON THE TERRITORY OF THE UKRAINIAN-POLISH BORDERLANDS IN 1944 – 1951 (the peer-review on the monograph: Artemyshyn Yu. Deportation Actions of the 1940s in the National Memory of the Ukrainians: State and Prospects of Research : monograph / NAS of Ukraine, I. Krypiakevych Institute of Ukrainian Studies. Lviv, 2023. 276 p.) - KRAVCHENKO, Lesya; SKOTNA, Nadiya (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
the peer-review on the monograph: Artemyshyn Yu. Deportation Actions of the 1940s in the National Memory of the Ukrainians: State and Prospects of Research : monograph / NAS of Ukraine, I. Krypiakevych Institute of Ukrainian Studies. Lviv, 2023. 276 p.